Gentle-BLUE: A New Method for Active Queue Management - Saaidah, A; Zalisham, M; Fadzli, M; Abdel-jaber, H (IEEE, 2024)
In this paper, early stage congestion control method at the router buffer is proposed. The proposed method, namely, Gentle BLUE (GB), extends the well-known BLUE method by providing a dynamic mechanism for calculating the dropping probability based on the status of the queue length. This dynamic-based overcomes the slow-to-congestion response shortage in the existing methods and provides better management for the router buffer. Unlike the original BLUE method, which has a slow response when sudden heavy congestion occurs as it uses fixed Pinc and Pdec values to adjust the dropping probability, the proposed method predicts congestion before it occurs and responds using dynamically updated values. The dropping value is dynamically calculated based on queue length and the remaining buffer capacity. The proposed GB method is simulated and the obtained results are compared with the existing Active Queue Management (AQM) methods namely, Random Early Detection (RED), Adaptive Gentle Random Early Detection (AGRED) and (BLUE) method. The comparison is conducted in terms of mean queue length (mql), queuing waiting time (D), throughput (T), packet loss (P-L) and dropping probability (D-P). The results show that the proposed method provides better queue length, better delayed queuing, and packet loss probability compared with the existing methods.